Prinsip Dasar Operasional Perbankan Syariah - Nur Izzati; Muhammad Yazid (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Banking fundamentals play an important role as a framework for all transactions in the field of Islamic finance, including muamalah. Free maghrib (maysir, gharar, haram, usury, and batil), trust and prudence in the administration of Islamic financial activities, and contract-based principles are the basic principles of Islamic finance. These three guidelines should be followed in various activities as they are based on Islamic sharia and the Qur'an and Hadith